IAptik-Khase - Bartenev, Edgar (Russia : St. Petersburg Documentary Film Studios, 2006)
A group of nomadic Nenets live in the Siberian tundra at "The End of the World", as the territory is known in the local dialect, traveling around the region with their reindeer herd. Yaptik-Hasse is one of the younger members of the extended Yaptik family. He is also their good spirit and therefore privileged to ride on a sacred sledge. Edgar Bartenev's film is a poetic contemplation of the rhythms of a life governed by the pulse of nature. The film offers an intimate portrait of a family as well as an insight into a nomadic culture.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films